Axiomatic Derivation of Scoring Rules Without the Ordering Assumption - Roger B. Myerson (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1993)
Earlier derivations of scoring rules, by Smith(1973) and Young(1975), assumed that a voter can express only a rank ordering of the alternatives on his or her ballot. This paper shows that scoring rules can be derived without this ordering assumption. It is shown that a voting rule must be a scoring rule if it satisfies three basic axioms: reinforcement, overwhelming majorities, and neutrality. Other range and nonreversal axioms are also discussed.
Keywords: 330